A GENERALIZED INTEGRAL-GEOMETRICAL THEORY IN MINING - Michail VULKOV (Fiabilitate şi Durabilitate)
A new mathematical model for mining through formation is suggested. A vector function whichdescribes the created displacement possibility of the influence zone points of the mining excavation is applied.The points put under influence react specifically to the offered displacement possibility. The reaction functionaldescribes their behavior. The cause-effect connection between the behavior of the displacement’s sources andthe reaction of the influence area points is described. The vector function of the source of displacement isobtained. The required simplification for mining out a coal seam is made. A new formula for determining thevertical displacement field is obtained.An approach is suggested which makes it possible to determine the rock mass reaction on basis of in-situmeasurements. The reaction of the rock mass of the created displacements possibility is determined analyticallyafter measurements of the displacements in a given mining field. This allows better calculation results to beobtained and offers an opportunity to adapt the calculating procedure to the unique conditions in a specificmining field.